Beyond business as usual: Portuguese enterprises in the age of sustainability megatrends - Zêzere, Ricardo Rodrigues da Silva (2023)
The unprecedented combination of social, environmental, and economic challenges, known as Sustainability Megatrends, has created comprehensive and sustainability-oriented changes across society. These megatrends are significantly impacting the political, economic, and environmental dimensions and are expected to have lasting effects in the coming decades. As a result, organisations face the increasing need to adapt and cope with these transformative forces to remain relevant and competitive. This study focuses on Portuguese organisations and their response to sustainability megatrends. A qualitative research methodology, followed by a set of secondary data of 101 interviews, revealed that Megatrends hold great relevance for Portuguese organisations. While the majority of organisations are currently implementing sustainable practices in their business strategy and adapting production to become more sustainable, It is evident that there is still progress to be made in order to fully embrace sustainability into their business model.